(untitled) (Malaysian Journal of Civil Engineering, 2018)
More and more empirical evidences have revealed the growing importance of the effects of fines towards the liquefaction susceptibility of sand matrix soils. The limiting value of the threshold fines content (fth) is an important criterion in influencing such behaviour. The positive hyperbolic relationship between fth and liquefaction resistance, in term of undrained shear strength of sand-non-plastic-fines mixtures have been proven right in previous academic publication. The aim of this paper is to examine whether such positive hyperbolic relationship would observable be as to sand-non-plastic-fines mixtures. Undrained triaxial compression tests were performed on specimens of sand with various percentages of plastic fines (kaolin) by weight. The threshold fines content of sand-kaolin mixtures was observed at 25% of kaolin by weight. The positive hyperbolic relationship was established for sand-kaolin mixtures. Coincidentally, the lowest undrained shear strength was observed at the threshold fines content of sand-kaolin mixtures. Hence, the concept of threshold fines content has been proven to be a corresponding factor for the undrained shear strength of both sand-non-plastic-fines mixtures and sand-plastic-fines mixtures.